2017
DOI: 10.5099/aj170100038
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Body Mass Index and Hematological Indices in Young Adult Nigerians with Different Hemoglobin Genotypes

Abstract: In view of the association of various haemoglobin electrophoretic patterns with different pathological conditions and obesity with its attendant risk factors for cardiac and pulmonary disorders, the present study evaluated the relationship between body mass index and haematological indices by randomly selecting young adult Nigerians with different haemoglobin electrophoretic patterns within the age group of 17-45 years and mean age of ±31 years old. 215 participants were enlisted for this study with their BMI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Reports from previous studies have revealed that a low BMI is associated with iron deficiency anaemia [13]. There were also the reports of no association between the red blood cells' counts, haemoglobin concentration, haematocrit and BMI [14,15]. Overweight, high BMI or/and high body fat is associated with low haemoglobin level in adolescent girls, while in boys such association was not found [16].…”
Section: Discussionmentioning
confidence: 93%
“…Reports from previous studies have revealed that a low BMI is associated with iron deficiency anaemia [13]. There were also the reports of no association between the red blood cells' counts, haemoglobin concentration, haematocrit and BMI [14,15]. Overweight, high BMI or/and high body fat is associated with low haemoglobin level in adolescent girls, while in boys such association was not found [16].…”
Section: Discussionmentioning
confidence: 93%
“…The mean ± SD and range of age in years, weight in kg, height in metres, body surface area in metre square, body mass index in kg/m 2 were 21.50 ± 3.52 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), 56.83 ± 10.67 (39-95), 1.63 ± 0.07 (1.48-1.81), 1.60 ± 0.14 (1.30 ±2.08), 21.33 ± 3.92 (15.42-38.54) respectively. This study showed that 12% were underweight, 66% had had normal weight, 10% had overweight and 3% had obesity.…”
Section: Resultsmentioning
confidence: 99%
“…Body mass index (BMI) is regarded as most popular among the anthropometric indices. It is an internationally accepted index for assessing obesity [19,20]. BMI is a measure of weight adjusted for height, calculated as weight in kilograms divided by the square of height in meters [20].…”
Section: Introductionmentioning
confidence: 99%
“…It may be due to hypertrophy and hyperplasia of adipocytes leading to release of inflammatory leucocytes. 2 Higher WBC count in obese individuals indicate an inflammatory process which has been suggested to play some roles in diseases including obesity, atherosclerosis, and other cardiovascular diseases. It may even suggest the onset of metabolic syndrome in obese subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity and elevated BMI are the major causes for development of chronic diseases like stroke, hypertension, Type 2 diabetes and other cardiovascular disorders. 2 Previous studies reported that obese individuals more susceptible to infections, and they have impaired granulopoiesis or reduced bacterial clearance upon infections. 3 These may suggest a negative effect on immunity and defense against infection as a result of overweight/obesity.…”
Section: Introductionmentioning
confidence: 99%